SPECIFICITY OF ANTIBODY BOVINE ZONNA PELLUCIDAE 3 (ANTI-bZP3) TO RABBIT ZP3 BASED ON bZP3 AS CONTRACEPTIVE ANTIGENS - Edwin Widodo; Aulanni’am Aulanni’am (Universitas Gadjah Mada, 2005)
Zonna pellucidae can be develop as antigen potential candidates based on reversible immunocontraceptive vaccines. Immunogenic sites of bovine zonna pellucidae 3 (bZP3) could stimulated the presence of anti-bZP3 which be located on rabbit ZP and inhibit sperm-egg interaction on fertilization process. Purpose of this research is to detect spesific binding anti-bZP3 to rabbit oocytes using dot blotting and ELISA method. Sub cutan induction of bZP3 with Freund's adjuvant, CFA (Complete Freund's Adjuvant) for initial immunization and following by IFA (Incomplete Freund's Adjuvant) at the 14th day and 39th day. Control female rabbit injected by Tris-Cl buffer diluted in Freund's adjuvant without bZP3 antigen. Rabbit serum injected to rat for producing Rat Anti Rabbit Anti-bZP3. This research concludes spesific binding of anti-bZP3 with increasing purple colour on dot blotting methods. Anti-bZP3 increasing on 24th day and 31th day and still until 48th day. Measurement with ELISA methods showed increased titer on OD405. Highest titer showed on 31th day post immunization. Anti-bZP3 synthetized by bZP3 induced on rabbit detectable by immunohistochemistry methods on late primary oocytes, early secondary oocytes, growing secondary oocytes, and oocytes on de Graaf folicular phase.